Frontispiece: Glyceride‐Mimetic Prodrugs Incorporating Self‐Immolative Spacers Promote Lymphatic Transport, Avoid First‐Pass Metabolism, and Enhance Oral Bioavailability. Issue 44 (21st October 2016) - Hu, Luojuan; Quach, Tim; Han, Sifei; Lim, Shea F.; Yadav, Preeti; Senyschyn, Danielle; Trevaskis, Natalie L.; Simpson, Jamie S.; Porter, Christopher J. H.
Abstract : Prodrugs In their Communication onpage 13700 ff., J. S. Simpson, C. H. J. Porter et al. report how the oral bioavailability of testosterone is significantly enhanced by generating glyceride‐based prodrugs that promote drug release and direct the drugs to the lymphatic system.